Reactive Jamming for Commercial Drones - Nam, Gyeong-Mo; Lee, Gun-Ho; Lee, Jae-Sin; Kil, Heang-Bok; Jeong, Eui-Rim (International Journal of Engineering and Technology, 2018)
Background/Objectives: Increasing use of UAVs causes many social problems. The purpose of this paper is to develop drone-jamming technique that protects social safety against indiscreet and illegal use of UAVsMethods/Statistical analysis:First, we analyze the frequency hopping pattern of the commercial drones in order to design jamming system. Specifically, the instantaneous Tx frequency is detected within several micro seconds. Therefore, the frequency analyzer tracks the communication frequency of the drone that changes every hop. After that, it transmits a strong jamming signal to the corresponding frequency, thereby disrupting the communication of the drones. All these procedures are completed in one-hop period, which enables reactive jamming.Findings: As commercial drones become widespread, drones are often used for malicious purposes. One example is the problem of drones flying into restricted areas. In this paper, we propose reactive jamming to disable unauthorized drones. The proposed method is as follows. When a jamming signal is transmitted to drones that use FHSS communication, the communication between the drones and the controller is disabled. In this case, we confirmed that the drone was switched to failsafe mode, and the connection to the drones was disabled on the controller screen. When the transmission of the jamming signal is turned off, the communication between the controller and the drone is connected again. When using the reactive jamming technique proposed in this paper, it is possible to prevent bomb terrorist, unauthorized reconnaissance, narcotics smuggling etc.Improvements/Applications: The conventional jamming method transmits a strongwideband interference for frequency hopping signals.The proposed reactive jamming technique, however, transmits a relatively weak interference signal to the narrow band to disable the frequency hopping communication.Â
Keywords: Reactive jammer; Commercial drone; Frequency hopping spread spectrum; Anti drone; real-time jammer